Photocatalytic degradation of organic pollutants through peroxymonosulfate activation: photocatalysts and reaction mechanisms - Silva, Roberta Resende Maciel da (Universidade Federal de São Carlos, 2023)
Water pollution from organic compounds has become a growing concern worldwide due to the risks imposed on human health and the environment. The rapid advancements in the pharmaceutical and agricultural industries have certainly improved our quality of life; however, the uncontrolled release of pharmaceuticals and pesticides into water bodies has become a serious problem. Even in small quantities, these pollutants have a detrimental impact on human health and pose a threat to the balance of aquatic ecosystems. Therefore, there is an urgent need to develop technologies that can efficiently remove these pollutants from wastewater. To address this problem, this thesis work focused on exploring the potential of two novel approaches based on the photocatalytic activation of peroxymonosulfate (PMS) for application in the remediation of water contaminated with organic compounds. In an attempt to develop cost-effective processes for industrial applications, the Co3O4 photocatalyst was applied to capture solar light to activate PMS for the degradation of the pesticide imidacloprid (IMD) in a continuous flow reactor. Under optimized conditions, 99% IMD photodegradation was achieved after two hours of operation. The outstanding performance of the Co3O4/PMS/solar irradiation process was attributed to the synergistic activation of PMS by Co2+ and Co3+ species in the Co3O4 catalyst and the ultraviolet (UV) component of solar irradiation, in either the homogeneous phase or after PMS adsorption onto Co3O4. It was found that the degradation mechanism of IMD in the Co3O4/PMS/solar irradiation system involved the formation of different oxidative reactive species (1O2, O2●−, and SO4●−), which were responsible for the oxidation of the pesticide. In a second approach, the g-C3N4/NiFe2O4 heterostructure was used to activate PMS under visible light (VL), for application in the degradation of a simulated wastewater containing tetracycline hydrochloride (TCH) as a model molecule of an organic pollutant. The photocatalytic tests revealed that the NiFe2O4/g-C3N4/PMS/VL system was successful in removing TCH over a wide pH range and in the presence of different anions commonly found in wastewaters. The superior degradation performance observed for the composite, compared to the pure oxides, was attributed to the synergism between heterojunction photocatalysis and PMS activation, generating the highly oxidizing 1O2, O2●−, and HO● species, responsible for effective degradation of TCH. Besides the fast kinetics, it also should be highlighted that the magnetic properties of the heterostructure facilitated separation of the photocatalyst for the purpose of reuse.
Degradação fotocatalítica de poluentes orgânicos pela ativação do peroximonosulfato: fotocatalisadores e mecanismos de reação
Keywords: Photocatalysis; Peroxymonosulfate; Organic Pollutants; Fotocatálise; Peroximonosulfato; Poluentes orgânicos; Co3O4; NiFe2O4/g-C3N4; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA